Effects of cabergoline on blood glucose levels in type 2 diabetic patients: A double-blind controlled clinical trial. Issue 40 (October 2016) - Bahar, Adele; Kashi, Zahra; Daneshpour, Ezzatossadat; Akha, Ozra; Ala, Shahram
Abstract: Background: Cabergoline is a long-acting agonist of dopamine, which has a high affinity to dopamine receptors (type 2). Treatment using a dopaminergic agonist reduces hypothalamic stimulation that increases during liver gluconeogenesis, lipids synthesis, and insulin resistance. Our aim was to evaluate the effects of cabergoline on blood glucose levels in patients with type 2 diabetes mellitus (DM). Methods: This study was a double-blind, controlled clinical trial in patients with type 2 DM. The patients received treatments of a placebo (control group; n = 20) or cabergoline 0.5 mg (cabergoline group; n = 20) using the sequential method, once per week for 3 months, while using previously prescribed glucose-lowering drugs. All tests, such as levels of fasting blood glucose, 2-hour post-prandial glucose, complete lipid profile, prolactin, alanine amino transferase, aspartate amino transferase, creatinine, blood urea nitrogen, and serum insulin, and homeostasis model assessment insulin resistance were measured at baseline and at 3-month follow-up. Results: The fasting blood sugar levels were significantly different between placebo and cabergoline groups after 3 months of treatment ( P  = 0.004). The prolactin levels were significantly different from beginning of the treatment to 6 months later ( P  = 0.001). In the cabergoline group, there was a significant decrease in glycosylated hemoglobin (HbA1C) levels after 3 months ( P  = 0.003). Overall, 65%and 45% patients in the cabergoline and control groups, respectively, responded to treatment (HbA1C<7%). Conclusion: Cabergoline may be useful as a long-acting antidiabetic agent in patients with type 2 diabetes mellitus.